IMPLEMENTASI RESTORATIVE JUSTICE TERHADAP TINDAK PIDANA PENGANIAYAAN DI KEJAKSAAN NEGERI BATU - Syauqi, Isam Dimas (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Restorative Justice has the meaning of restoring the relationship as before and also as an atonement for various violations committed by the offender of a criminal act against the victim who was harmed by the criminal act carried out outside the judicial process which has the aim that legal problems caused by criminal acts by the perpetrator allow it to be resolved outside the judiciary fairly with the agreement and agreement of all parties involved, namely the victim, the perpetrator, and the community. This study aims to determine the general description and implementation of the implementation of Restorative Justice in the realm of the State Attorney’s Office, and to review its suitability from the Attorney General’s Regulation No. 15 of 2020 related to the main points and Basic Guidelines for Strategy and Implementation of termination of prosecution based on restorative justice